Self-reported physical activity behavior of breast cancer survivors during and after adjuvant therapy: 12 months follow-up of two randomized exercise intervention trials - Schmidt, Martina; Wiskemann, Joachim; Schneeweiss, Andreas; Steindorf, Karen (Acta oncologica, 2017)
Background: Exercise during and after breast cancer treatment has shown several health benefits. However, little is known about the courses, patterns, and determinants of physical activity of breast cancer patients, and the role of exercise interventions on their physical activity behavior in the long run.Material and methods: Self-reported physical activity was assessed in 227 breast cancer survivors before, during, and three, six, and 12 months post-intervention within two randomized resistance exercise trials performed during adjuvant chemo- or radiotherapy, respectively, with similar designs. Multiple ordinal logistic regression analyses were performed to identify determinants of physical activity at these time points.Results: While the intervention group exercised a median 1.8 h/week during adjuvant therapy (interquartile range 1.4-2.5), 68% of controls did not engage in any exercise. At 12-months follow-up 32% of patients did not engage in any exercise irrespective of the intervention. Of the patients who cycled for transportation pre-diagnosis about half stopped cycling in the long term in both groups. In contrast, walking was maintained over time. Major determinants of low levels of exercise at 12-months follow-up were low pre-diagnosis levels of exercise, lower education, being postmenopausal, and having breast problems or depressive symptoms. Further, the intervention appeared to influence the type of sports performed, with strength exercise being the most common type of exercise at follow-up in the exercise group, more frequently compared to the control group.Conclusion: The exercise intervention effectively countervailed the decrease in physical activity during cancer therapy and boosted strength exercise in the months following the intervention, but in the longer term many survivors were insufficiently active. Breast cancer survivors may need continued motivation and practical support tailored to their individual characteristics and physical activity history to incorporate exercise in everyday routine in the long term.
Gesehen am 24.05.2018